2012
DOI: 10.1386/ijcm.5.2.155_1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived benefits of active engagement with making music in community settings

Abstract: This article focuses on the reported benefits of participation in music activities, identified by participants of the Music for Life Project. The participants engaged in weekly music activities offered in three locations: two centres in London and one in the North of England. Their responses were collected through questionnaires and focus group interviews. Music participants attributed improvements in quality of life to active engagement with music, and a wide range of cognitive, social, emotional and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 0 publications
3
35
0
2
Order By: Relevance
“…Overall, when questioned about what was special about music as opposed to other activities, many participants attributed positive benefits to the creative and expressive qualities of music. [ 18,19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Overall, when questioned about what was special about music as opposed to other activities, many participants attributed positive benefits to the creative and expressive qualities of music. [ 18,19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Our findings show that this presenting to others appears only in the last phase. Regarding the preparation tools, it appears that students report making greater use of recordings as their expertise develops (Hallam et al, 2012). However, recordings or performing for others could be used sooner in order to optimize the time the students have to prepare for a performance exam.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported that community musical theatre offers socially and musically meaningful experiences, similar to the social support found by Carucci (2012) in adult community bands and Hallam et al (2012) in the Music for Life Project. Beyond this, community musical theatre offers opportunities for different generations to interact in participant experiences with results similar to those reported by Varvarigou et al's (2001) intergenerational project where people over 50 participated in structured musical opportunities with students in two East London primary schools.…”
Section: Overview Of the Ethnographymentioning
confidence: 58%